Weaving sociality: designing social infrastructure for disaster resilience - Jennings, Caleb (Kansas State University, 2024)
As disaster events become increasingly prevalent and intense, people are becoming more isolated, and social networks are weakening. Poor social connections to one’s community puts individuals at elevated risk during times of disaster. Existing research argues that social infrastructure, places that bring people together and encourage social interactions, can help improve social networks, contributing to more disaster-resilient communities. This study builds off past works by exploring how access to social infrastructure sites, both actual and perceived, affects the disaster resilience of the South Providence Community in Providence, RI. This study aims to answer three questions: (1) What social infrastructure typologies are most capable of improving community cohesion and social networks? (2) How accessible are social infrastructure sites within the community, and what are the perceived and actual barriers to them? (3) How can social infrastructure be designed to best improve the social networks of a community? These questions were answered using literature reviews, GIS-based spatial analysis, and interviews. Ultimately, this study proposes a vision plan and designed social infrastructure sites for improving social networks and disaster resilience in South Providence. The research and design outcomes were synthesized into a report that discusses the role of social networks in a disaster-resilient community and shows how improved social infrastructure sites and network building between them improve a community's disaster resilience.
Keywords: Disaster resilience; Social infrastructure; Community; Landscape architecture